Arabic And It’s Place In The Tradition of Multilingual Lexicography In Case of Edmund Castell’s Lexicon Heptaglotton - ACAR, Ömer (Scientific Journal of Faculty of Theology, 2013)
This study outlines the place of Arabic in the tradition of multilangual dictionary. Especially the levels of the Arabic language dictionary writing that an important part of Arabic studies which in center of European orientalist studies and E. Castell`s voluminous work is the basis of this study. Initially, most of the commercial and economic concerns, multilingual dictionaries prepared in the form of word lists developed important services, especially in the field of translation. The word lists of the Sumer-Babil-Asur languages are considered as ancestor of multilingual dictionaries. As a member of this family Arabic language has an important condition in this area.